2-Sulfoethylammonium Trifluoromethanesulfonate as an Ionic Liquid for High Temperature PEM Fuel Cells. Issue 2 (3rd November 2015) - Wippermann, K.; Wackerl, J.; Lehnert, W.; Huber, B.; Korte, C.
Abstract : 2-Sulfoethylammonium trifluoromethanesulfonate ([2-Sea + ][TfO − ]) represents a novel class of proton-conducting ionic liquids (PILs) based on aminoalkylsulfonic acids. The fundamental suitability of [2-Sea + ][TfO − ] for application as a protic electrolyte in high temperature PEM fuel cells (HT-PEFCs) was investigated up to a temperature of 130°C. A comparison was made against a state-of-the-art electrolyte, phosphoric acid. [2-Sea + ][TfO − ] is electrochemically and thermally stable up to 140°C. The specific conductivity of 95 wt% [2-Sea + ][TfO − ] aqueous solution at 130°C is ≈20 times lower compared to 95 wt% H3 PO4 . The strong coupling of ion transport and viscous flow suggests a vehicular ion (proton) transport in [2-Sea + ][TfO − ]. 95 wt% [2-Sea + ][TfO − ] shows superior kinetics in terms of oxygen reduction reaction (ORR) on polycrystalline Pt compared to 95 wt% H3 PO4 at temperatures greater than 90°C in a fuel cell-applicable potential range. Double layer capacitances suggest a complex double layer structure, including adsorbed [2-Sea + ][TfO − ] and water, as well as intermediates of oxygen reduction and Pt oxidation. Potential and temperature-dependent ORR kinetics in the presence of 95 wt% [2-Sea + ][TfO − ] yield different Tafel slopes (b = 82–139 mV) and symmetry factors (β = 0.46–0.96), indicating changes in surface coverages of the adsorbed species and possibly also a change in the reaction mechanism.